2014
DOI: 10.1016/j.brainres.2014.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Altered brainstem auditory evoked potentials in a rat central sensitization model are similar to those in migraine

Abstract: Migraine symptoms often include auditory discomfort. Nitroglycerin (NTG)-triggered central sensitization (CS) provides a rodent model of migraine, but auditory brainstem pathways have not yet been studied in this example. Our objective was to examine brainstem auditory evoked potentials (BAEPs) in rat CS as a measure of possible auditory abnormalities. We used four subdermal electrodes to record horizontal (h) and vertical (v) dipole channel BAEPs before and after injection of NTG or saline. We measured the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…As previous studies have suggested [3335], there were no differences in auditory brainstem click responses between groups during the migraine interictal period. However, other authors found significant differences [36, 37].…”
Section: Discussionsupporting
confidence: 63%
“…As previous studies have suggested [3335], there were no differences in auditory brainstem click responses between groups during the migraine interictal period. However, other authors found significant differences [36, 37].…”
Section: Discussionsupporting
confidence: 63%
“…In preclinical rodent models of migraine, NTG-induced central sensitization is a well-characterized model that has demonstrated increased brain sodium levels [24], hypersensitivity to pain based on behavioral response [18,24,28,31,53], altered cerebral blood flow [22,27], increased cFos expression in the trigeminal nucleus caudalis (TNC) [24,54], increased expression of nitric oxide synthase [21,42] and abnormalities in brainstem auditory evoked potentials (BAEPs) of rats [4]. In clinical cohorts, NTG administration triggers a mild immediate headache, which is stronger in migraine sufferers than in healthy subjects and derives from the acute vasodilatory effects of nitric oxide (NO) impacting the cerebral vasculature.…”
Section: Resultsmentioning
confidence: 99%
“…There is considerable evidence that the administration of nitric oxide (NO) donors, such as NTG, in humans induces headaches similar to those in migraine attacks (11, 20). As such, NTG-induced sensitization is a widely accepted migraine model in rodents (5,79), as well as humans (10). In preclinical models, NTG causes allodynia and hyperalgesia (21), brain sodium elevation and activation of cFos in the trigeminal nucleus caudalis neurons (TNC) (5), and abnormalities in the brain stem auditory evoked potentials of rats (7).…”
Section: Methodsmentioning
confidence: 99%
“…It follows that the identification of specific metabolic changes may improve understanding of migraine and open new avenues for therapy development. This study, therefore, evaluates biochemical and metabolic imbalances hypothesized to reflect dysfunctional pathways paralleling migraine impacts in humans by means of a frequently studied nitroglycerin (NTG) triggered animal migraine model (5, 79). In clinical cohorts, NTG typically triggers a mild headache that is short-lived and stops rapidly after administration is completed, based on a short (2-min) half-life (10, 11).…”
Section: Introductionmentioning
confidence: 99%